2021
DOI: 10.1371/journal.pone.0250087
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and subjective happiness between the ages 40 and 59 in relation to presbyopia and dry eye

Abstract: Purpose The aim of this study was to explore the status of quality of life between the ages 40–59 in relation to presbyopia and dry eye. Methods Near add power and preferred contact lens power were examined in 219 participants at three clinics. 2000 participants completed a web-based survey on presbyopic symptoms, symptomatic dry eye, sleep quality, and subjective happiness. Results Mean preferred corrected visual acuity was less than 20/20 in women (vs men, P<0.01) who were more often prescribed under-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In a smaller prospective study, also based in Japan, awareness of presbyopia was present in 50 % of participants aged 45–49 years, rising to 87.5 % in those aged 50–54 years and 100% in the 55–59 years age group. 13 None of the 15 participants aged 44 years and under were aware of presbyopia, in contrast to the report of Negishi et al 40 where 38% of respondents indicated that that they had become aware of difficulties focusing before 40 years of age, although these data were based on historical recall. Notably, the work of Tsuneyoshi et al 13 highlighted that patient awareness of presbyopia and difficulty with near tasks increased dramatically when binocular near visual acuity with habitual correction reduced to 0.0 logMAR (20/20); at this level, more than 80 % of patients were aware of presbyopia, and most had difficulty reading a newspaper or reading a book for an extended period.…”
Section: The Patient Experience Of / Journey Through Presbyopiamentioning
confidence: 66%
See 1 more Smart Citation
“…In a smaller prospective study, also based in Japan, awareness of presbyopia was present in 50 % of participants aged 45–49 years, rising to 87.5 % in those aged 50–54 years and 100% in the 55–59 years age group. 13 None of the 15 participants aged 44 years and under were aware of presbyopia, in contrast to the report of Negishi et al 40 where 38% of respondents indicated that that they had become aware of difficulties focusing before 40 years of age, although these data were based on historical recall. Notably, the work of Tsuneyoshi et al 13 highlighted that patient awareness of presbyopia and difficulty with near tasks increased dramatically when binocular near visual acuity with habitual correction reduced to 0.0 logMAR (20/20); at this level, more than 80 % of patients were aware of presbyopia, and most had difficulty reading a newspaper or reading a book for an extended period.…”
Section: The Patient Experience Of / Journey Through Presbyopiamentioning
confidence: 66%
“…Patient experience of, and progression through presbyopia may be influenced by factors including sex, ethnicity and refractive correction. In a large scale survey of 2000 presbyopes in Japan, the mean age at which symptoms such as ‘hard to see small letters up close’ and ‘see better when I increase distance from the object’ were first experienced ranged between 43.9 years and 46.7 years, with males becoming aware of symptoms at a younger age than females and experiencing a greater burden on near vision 40. Accompanying clinical data from contact lens wearers indicated that females were more likely to tolerate early presbyopia through undercorrection of myopic refractive errors, compared with males who preferred full myopic correction.…”
Section: The Patient Experience Of / Journey Through Presbyopiamentioning
confidence: 99%
“…In a cross-sectional study, poor sleep quality was reported to be associated with the symptoms of DED ( 4 ). Several other independent studies have also reported the potential association between sleep quality and DED severity ( 12 , 32 , 33 ). In this case–control study, only the OSA group showed a relationship between poor sleep quality and higher DED risk and not the control group.…”
Section: Discussionmentioning
confidence: 92%
“…Presbyopia is a presentation of near vision focusing difficulty while under full correction of distance vision, and it is a global burden for health and the economy in super-aging societies ( 1 4 ). Recent investigations found presbyopia was associated with subjective happiness, sleep quality ( 5 ), quality of life ( 6 ) and visual disability. Presbyopia is a consequence of aging and should inevitably progress alongside other aging events.…”
Section: Introductionmentioning
confidence: 99%